Pedagogical Thinking in Pragmatism John Dewey (Raparin Journal of Humanities (RJH), 2021)
The process of life is linked to continuity and survival among all the organisms, and human being in nature are the most intelligent living organism unlike all other organisms in the sense that he is a social being since he desires to live in civilized life. By civilized life we mean a life where all individuals live in society for the sake of fulfilling the diverse needs they are unable to fulfill by themselves, because survival and continuity is not uneasy task since they constantly changing and increasing, so the members of a given society have to take the responsibility for achieving each other’s needs. The concept of education in the human society is said to be more different and extensive than other living things is because this process consists of developing mature members for the society, so that they can take the responsibility placed on them by that the society.The function of education is to determine the most appropriate methods, which are represented by the educational thinking of the thinkers and philosophers who organize the process of education and its suitability in a way that is compatible with all times, environment and. Pragmatism is considered as one of the approaches that has a great role in solving problems taking place among communities, so that education becomes a tool for solving problems associated with the human social live.